2005
DOI: 10.1002/lsm.20257
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of a traditional pulsed dye laser versus a long‐pulsed dye laser in the treatment of early childhood hemangiomas

Abstract: Background and Objective: The role of pulsed dye laser (PDL) in the treatment of childhood hemangiomas is still controversial because of the inherent characteristics of hemangiomas as well as the side effects of the PDL. Recently, the long pulsed dye laser (LPDL) with cryogen spray cooling (CSC) has been found relatively more effective and safer than the PDL in the treatment of portwine stains and telangiectasia. This study was designed to compare the efficacy and complication rate of PDL versus LPDL for treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 15 publications
3
58
0
4
Order By: Relevance
“…Several hypotheses have been proposed concerning the process of haemangiogenesis, including the possible role of somatic mutation in one or more components of critical vascular growth-regulatory pathways (Walter et al 2002). The high endothelial cell proliferation and turnover and the high mitotic activity during the proliferation of haemangiomas suggest that these lesions should be considered as tumours (Ethunandan and Mellor 2006;Kono et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses have been proposed concerning the process of haemangiogenesis, including the possible role of somatic mutation in one or more components of critical vascular growth-regulatory pathways (Walter et al 2002). The high endothelial cell proliferation and turnover and the high mitotic activity during the proliferation of haemangiomas suggest that these lesions should be considered as tumours (Ethunandan and Mellor 2006;Kono et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although this difference was not statistically significant, the group treated with PDL had significantly more hypopigmentation (3.12% vs. 8.31%; p = 0.001), more hyperpigmentation (2.8% vs. 4.15%; p = 0.005), and more textural changes (1.4% vs. 6.23%; p = 0.001). Finally, the average time period of maximum proliferation in the LPDL group was significantly shorter [23] . Recently, a comparison study was carried out in order to identify the earlier regression, the prevention of further proliferation, and the achievement of a better cosmetic outcome using PDL treatment in comparison to observation only (-wait-and-see approach‖).…”
Section: Cutaneous Haemangiomasmentioning
confidence: 83%
“…75 The PDL has been used and studied for more than 30 years as an option for treatment of IHs, and, as a result, there is substantial level III-V evidence in the form of various case reports, retrospective reviews, and small, nonrandomized prospective studies supporting its efficacy in the literature. [76][77][78][79][80][81][82][83] In 2002, the first level III evidence comparing PDL therapy to observation in the treatment of IHs was performed by Batta and colleagues 84 and raised significant doubt surrounding its efficacy. The investigators' analysis revealed no benefit in the number of children whose lesions showed complete clearance or minimal residual signs at 1 year in the PDL versus observation group.…”
Section: Pulsed Dye Laser Therapymentioning
confidence: 99%